Improving surgical outcomes through non-technical skills: the case for better training and national evaluation - Sidhu, Gur Aziz Singh; Dekker, Andrew; Nagra, David; Stammer, Adam; Bhamra, Jagmeet Singh; Ashwood, Neil (International Journal of Research in Orthopaedics, 2025)
Effective communication and teamwork are as crucial as technical proficiency for achieving positive surgical outcomes. Non-technical skills (NTS)-including communication, leadership, decision-making, and situational awareness—enhance surgical performance by fostering awareness and capability among both trainees and experienced surgeons. Despite growing recognition of its importance, NTS training is not uniformly implemented in surgical education, leaving a significant gap. This study examines opportunities to expand NTS training within surgical practice. A survey at a local hospital assessed the availability of NTS training and perceived needs among 38 surgical trainees and professionals. The majority acknowledged the value of NTS in improving clinical performance but reported limited focus on human factors in daily practice. Complementing the survey, a literature review was conducted across Medline, EMBASE, and PsycINFO databases, identifying 414 relevant articles, 114 of which focused on clinical or educational contexts. Of these, 61 studies emphasized psychomotor skill assessment via direct observation, patient outcomes, and peer feedback, underscoring the critical role of effective evaluation methods. Findings indicate that while NTS training is appreciated, its effectiveness depends heavily on feedback quality and team dynamics, particularly in addressing challenging behaviors. The study highlights the need for enhanced training design and robust feedback mechanisms. Although current evidence linking NTS training to improved patient outcomes is largely anecdotal, there is strong professional support for broader implementation. The authors advocate for a systematic, nationwide evaluation to determine the true impact of NTS training on surgical performance and outcomes.